2000
DOI: 10.1034/j.1399-3003.2000.16d21.x
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of circulating adhesionmolecules in bronchiectasis

Abstract: Adhesion molecules are expressed on the surface of endothelial cells and leukocytes and are responsible for mediating the migration of intravascular leukocytes into inflamed tissue. Intensive recruitment of neutrophils into the airways occurs in bronchiectasis, although little is known about the role of adhesion molecules in this process.The authors, therefore, determined serum levels of E-selectin, intercellular adhesion molecule (ICAM)-1 and vascular adhesion molecule (VCAM)-l in stable bronchiectasis patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
3

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 31 publications
0
24
0
3
Order By: Relevance
“…25,26 Circulating sICAM-1, sVCAM-1, and sE were increased in children with acute asthma, stable asthma, and acute bronchiolitis and their expressions are more pronounced in asthmatic patients than in control subjects. [27][28][29][30][31] In a very recent study by Kose et al, the higher level of sICAM-1 was observed in mild and/or moderate asthmatic children than in healthy subjects. 32 The difference may be caused by the differences of severity and type of asthma (e.g., allergic or nonallergic, with or without bronchial hyperreactivity).…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Circulating sICAM-1, sVCAM-1, and sE were increased in children with acute asthma, stable asthma, and acute bronchiolitis and their expressions are more pronounced in asthmatic patients than in control subjects. [27][28][29][30][31] In a very recent study by Kose et al, the higher level of sICAM-1 was observed in mild and/or moderate asthmatic children than in healthy subjects. 32 The difference may be caused by the differences of severity and type of asthma (e.g., allergic or nonallergic, with or without bronchial hyperreactivity).…”
Section: Discussionmentioning
confidence: 99%
“…It has been known for some time that patients with bronchiectasis also present a systemic inflammatory response [1] including up-regulated expression of circulating leukocyte adhesion molecules [10] even when clinically stable. The former analysis of differential leukocyte count, CRP, erythrocyte sedimentation rate and serum immunoglobulins in 87 patients reported significant associations between systemic 14 inflammation and bronchiectasis severity as assessed both by CT scan and lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Table 2 presents We next went on to explore differences by disease severity (BSI and FACED score) and aetiology in patterns of these components, using the first key cytokine associated with that component. In both the total derivation cohort and the selected patients with post-infectious aetiology, there was a step-wise increase in fibrinogen from mild through moderate to severe patients, 10 but significant heterogeneity in the other four markers. Reflecting this, in the whole derivation cohort, we observed a significant correlation between the plasma fibrinogen concentration and BSI score (rho=0.34, p=0.001, Figure 2A).…”
Section: Principal Component Analysismentioning
confidence: 99%
“…Their bronchoalveolar lavage fluid contains increased levels of neutrophils, elastase, myeloperoxidase, tumour necrosis factor (TNF)α, interleukin (IL)-8 and IL-6 compared with controls 54. Serum levels of adhesion molecules E-selectin, intercellular adhesion molecule-1 and vascular adhesion molecule-1 are also raised, with the former two inversely related to forced expiratory volume in 1 s (FEV 1 ) 55. Those with more severe bronchiectasis (earlier diagnosis, lower FEV 1 and varicose-cystic bronchiectasis) are more likely to be colonised with pathogens56 and have more intense inflammation than those not colonised 54.…”
Section: Pathogenesis Of Exacerbationsmentioning
confidence: 99%